Evaluation of Neutrophil Gelatinase-Associated Lipocalin as a Predictor of Glomerular Filtration Rate and Amikacin Clearance During Early Rat Endotoxemia: Comparison with Traditional Endogenous and Exogenous Biomarkers - Studená, Šárka; Doleželová, Eva; Cermanová, Jolana; Prašnická, Alena; Springer, Drahomíra; Mičuda, Stanislav; Chládek, Jaroslav (European journal of drug metabolism and pharmacokinetics, 2020)
BACKGROUND AND OBJECTIVES: Renal elimination of amikacin and other aminoglycosides is slowed down in sepsis-induced acute kidney injury increasing the risk of adverse effects. Since neutrophil gelatinase-associated lipocalin (NGAL) and aminoglycosides share the mechanisms for renal excretion, the predictive power of NGAL was examined towards the changes in amikacin pharmacokinetics during early endotoxemia in anesthetized Wistar rats. METHODS: Endogenous biomarkers of inflammation and acute kidney injury were assessed including NGAL in saline-injected controls and two groups of rats challenged with an intravenous injection of bacterial lipopolysaccharide (5 mg/kg)-a fluid-resuscitated group (LPS) and a fluid-resuscitated group infused intravenously with 8 μg/kg/h terlipressin (LPS-T). Sinistrin and amikacin were infused to measure glomerular filtration rate (GFR) and amikacin clearance (CLam). The investigations included blood gas analysis, chemistry and hematology tests and assessment of urine output, creatinine clearance (CLcr) and sinistrin clearance (CLsini). RESULTS: Within 3 h of injection, systemic and renal inflammatory responses were induced by lipopolysaccharide. Gene and protein expression of NGAL was increased in the kidneys and the concentrations of NGAL in the plasma (pNGAL) and urine rose 4- to 38-fold (P < 0.01). The decreases in CLam and the GFR markers (CLcr, CLsini) were proportional, reflecting the extent to which endotoxemia impaired the major elimination mechanism for the drug. Terlipressin attenuated lipopolysaccharide-induced renal dysfunction (urine output, CLcr, CLsini) and accelerated CLam. The pNGAL showed a strong association with the CLsini (rs = - 0.77, P < 0.0005). Concerning prediction of CLam, pNGAL was comparable to CLcr (mean error - 24%) and inferior to CLsini (mean error - 6.4%), while the measurement of NGAL in urine gave unsatisfactory results. CONCLUSIONS: During early endotoxemia in the rat, pNGAL has a moderate predictive ability towards CLam. Clinical studies should verify whether pNGAL can support individualized dosing of aminoglycosides to septic patients.
Keywords: lipokalin-2; modely u zvířat; mužské pohlaví; krysa rodu Rattus; Male; oligosacharidy; prediktivní hodnota testů; Glomerular Filtration Rate; metabolická clearance; Inflammation; ledviny; zánět; Kidney; Lipocalin-2; Acute Kidney Injury; Rats; Amikacin; Endotoxemia; Lipopolysaccharides; potkani Wistar; moč; Urine; akutní poškození ledvin; endotoxemie; Animals; Predictive Value of Tests; Biomarkers; biologické markery; lipopolysacharidy; zvířata; Sepsis; hodnoty glomerulární filtrace; Cytokines; Models, Animal; Rats, Wistar; sepse; amikacin; cytokiny; Oligosaccharides; Metabolic Clearance Rate